Implementation of KAP Communication Model in Improving Interpersonal Communication Skill of Children with Special Needs - PUTRI EKARESTY HAES (JCommsci - Journal Of Media and Communication Science, 2019)
Article 31, paragraph (1) of the 1945 Indonesia Constitution said that every citizen has a basic right to education. The law creates a framework for the main educational goals, policies, and plans as well as aims to make education relevant to the needs of the community. It also provides the rights and obligations of citizens to get full education without discrimination including children with disabilities or children with special needs. The KAP (Knowledge, Attitude, and Practice) communication planning model is divided into three phases. The first phase is targeting the audience, messages and communication channels. The second phase is planning to design messages, produce the media (drafting) and make the trial. The third phase includes changing the knowledge, attitudes, and practice of targets that are expected to be carried out by teachers and therapists. KAP communication planning model is intended to improve the interpersonal communication of children with special needs both in the teaching and learning process and also in their daily lives in the family and community.